ANTI-PAIN MEDICINE AVAILABILITY IN THE WONOASRI DISTRICT PHARMACY, MADIUN REGENCY - Astuti, Endah Astuti; Astuti, Risma Sakti Pambudi; Astuti, Rita Septiana (Borneo Journal of Pharmascientech, 2020)
Pain is a disease experienced by all people. Analgesics are a class of drugs most often used for the treatment of pain. Good planning was needed as a basis for drug management activities to determine drug needs to ensure the availability of painkillers. This study aims to provide an availability of analgesic drugs in 3 (three) pharmacies in Wonoasri District, Madiun Regency.This research was a descriptive study using a retrospective survey method, which was directed at presenting information about the availability and use of painkillers through the research process. The data were obtained from the Pharmacy in Wonoasri District, Madiun Regency. This research material was in the form of data on drug availability and data on the use of painkillers for the period July to December 2019. The data obtained were then processed using the formula for the number of drugs available divided by the number of monthly average usage. The level of drug availability was seen in months.Based on the results of the study, it was found that the value of the availability of painkillers at the Pharmacy of Wonoasri District, Madiun Regency for the period July-December 2019 was the Diclofenac drug with an availability value of 7.8 months, 9.1 and 13.1 months. While the lowest is Mefenamic Acid Drug. Medicines provided for health services at the pharmacy must match the drug needs and must be at least the same as the stock during the waiting time for drug arrival